Asam Lemak Omega-3 Dan Hubungannya DenganPenyakit Kardiovaskular - Ririn Anjelin; Nadia Raihana; Maimum; Fefri Ferianti; Harry Saputra (Program Studi Farmasi UNAJA, 2022)
Cardiovascular diseases are the number one global cause of death, the two most common are coronaryartery disease and stroke. Data suggests that high omega-3 consumption has a benefit in preventingcardiovascular diseases. The report of observations, clinical , animal and in vitro studies havedemonstrated the benefits of omega-3 prevent and treat cardiovascular disease. Although the mechanismis not clear, but it has been shown that the cardiovascularprotection effect of omega-3 fatty acids may becaused by its role influencing biological effects on lipid and lipoprotein metabolism, platelet function,arterial cholesterol distribution, vascular function and inflammatory response.